RELATIONSHIP BETWEEN LEVEL STRESS WITH ELDERLY QUALITY SLEEP IN VILLAGES DUKUH SUBSCRIPTION BANYUDONO REGENCY OF BOYOLALI - Yuni Astuti; Witriyani .; Akbar Amin Abdullah (STIKES DUTAGAMA KLATEN, 2018)
Background: According to WHO (2013), the elderly population in 2050 is estimated to increase threefold from 2013. The elderly will experience physical changes such as sight and hearing impairment as well as sleep disorder or hard to sleep. Sleep quality is influenced by several factors,such as disease, fatigue, medicine, and stress. According to APA (2013), about 42% of adults report having poor sleep quality and 43% report that stress has caused staying awake at night. Objective: The objective of this study is to determine the correlation between stress level and sleep quality of elderly at Dukuh Village, Banyudono Sub-District, Boyolali District Research Method: This study is a kind of quantitative correlation with cross sectional approach. The population of this study is all elderly at Dukuh, Banyudono, Boyolali which amounts to 434 elderly. The sample was taken by using purposive sampling. The instrument used in this study is the PSS 14 (Perceived Stress Scale 14) and the PSQI (Pittsburg Sleep Quality Index) questionnaire. The data were analyzed using chi square test. Results: The respondents' characteristics were 60 – 65 years old (32.9%), female (58.5%), male (41,5%), housewife (32.9%), and elementary school educated (36.6%). Most elderly have low stress (42,7%) and have poor sleep quality (74,4%). Chi Square obtained a value of 0.000 (p <0.05). Conclusion: There is correlation between stress level and sleep quality of elderly at Dukuh, Banyudono, Boyolali